Mental state of medical students three years into the war - V. V. Ogorenko; A. V. Shornikov; V. O. Kokashynskyi; O. A. Makoviichuk; O. E. Kachan (Zaporožskij Medicinskij Žurnal, 2025)
The aim of the study was to assess the mental health status of higher medical education students three years into the war in Ukraine.